Influence of Resveratrol Against Ovariectomy Induced Bone Loss in Rats: Comparison With Conjugated Equine Estrogen Tibolone and Raloxifene - Çelik, Ömer; Hasçalık, Şeyma; Tamser, Mustafa; Türköz, Yusuf; Kekilli, Ersoy; Yağmur, Cengiz; Boz, Mehmet (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: We examined the effect of resveratrol, a phenolic compound found in the skins of most grapes, on bone loss in ovariectomized rats. STUDY DESIGN: A total of 42 young Wistar-albino rats, of which 35 animals were submitted to bilateral oophorectomy, and 7 rats were submitted to the same surgical incision but without oophorectomy were studied. The rats were assigned to six groups of 7 animals each. For 35 consecutive days the following treatments were given: Group 1, sham; group 2, ovariectomized (OVX); group 3, OVX plus resveratrol; group 4, OVX plus conjugated equine estrogen; group 5 OVX plus tibolone; group 6, OVX plus raloxifene. Immediately 40 days after the ovariectomy bone mineral density (BMD) of the lumbar spine and femur by using dual-energy X-ray absorptiometry. The BMD of lumbar region (R1), total femur region (R2) and three neighbor subregions of femur (R3, R4, R5) were drawn. RESULTS: There were no significant difference between OVX and resveratrol groups for R2, R3 and R4 values. Compared with the OVX group, CEE group had lower values for R3 but similar values for R2 and R4. Raloxifene group had significantly higher value than the OVX, resveratrol, CEE and tibolone groups for R2. For R3, raloxifene had significantly higher values than in the ones in resveratrol, CEE and tibolone. For R4 region, raloxifene had significantly higher values than CEE group. CONCLUSION: Resveratrol administered to ovariectomized rats for 35 days had not a beneficial effect on the development of osteopenic skeletal changes.